High sensitivity hydrogen sensor based on tilted fiber Bragg grating coated with PDMS/WO3 film. (29th January 2022) - Zhang, Chong; Chen, Xiaoman; Liu, Xiaohang; Shen, Changyu; Huang, Zhenlin; Wang, Zhihao; Lang, Tingting; Zhao, Chunliu; Zhang, Yueming; Liu, Zugang
Abstract: A hydrogen sensor based on tilted fiber Bragg grating (TFBG) coated with PDMS/WO3 composite film was proposed. The WO3 powder can be adhere well to the surface of TFBG by the flexible PDMS film. The exothermic reaction between WO3 and hydrogen made the effective refractive index of the cladding of the TFBG change, and the intensities of cladding modes coupled from the core mode changed accordingly. The proposed fiber hydrogen sensor showed the sensitivity of 0.596 dB/% under the hydrogen concentrations from 0% to 1.53%. The average response time and recovery time of the sensor were 93 s and 107 s, respectively. Moreover, the TFBG based sensor can be made inherently temperature self-compensation by referencing all cladding-mode wavelengths to the wavelength of the core mode resonance of the grating, which is isolated from the effective refractive index changes of the fiber surroundings. Highlights: High sensitivity hydrogen sensor based on tilted fiber Bragg grating coated with PDMS/WO3 film was proposed. The proposed sensor's sensitivity of 0.596 dB/% is almost 6 times higher than that of the current similar sensor. Intensity demodulation method can help to reduce the cost of the sensor. The proposed sensor has the characteristic of the temperature self-compensation.